1959
DOI: 10.1063/1.1730553
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Heat Capacity of Azurite

Abstract: The electron-spin resonance of F centers in potassium iodide is observed at 293°K, 77°K, and 4°K. Addibvely-c~lored crystals of several concentrations and x-rayed crystals show the same resonance with g= 1.970 and a width of 213 gauss at maximum slope. The saturation of the absorption is measured. The resonances of F centers in potassium halides are compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
12
0

Year Published

1961
1961
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 6 publications
5
12
0
Order By: Relevance
“…Our experimental azurite heat capacity data are shown in Fig. 2 a together with the curve of Forstat et al (1959). The curves overlap satisfactorily.…”
Section: Comparison Of Malachite and Azurite Thermochemical Constantssupporting
confidence: 53%
See 2 more Smart Citations
“…Our experimental azurite heat capacity data are shown in Fig. 2 a together with the curve of Forstat et al (1959). The curves overlap satisfactorily.…”
Section: Comparison Of Malachite and Azurite Thermochemical Constantssupporting
confidence: 53%
“…To these results for azurite between 3.8-300 K we added the experimental heat capacity data of Forstat et al (1959) (temperatures 1.76-3.6 K) who had observed a 2-shaped anomaly at 1.84K (Fig. 2a).…”
Section: Calculation Of Thermodynamic Data Of Azurite and Malachitementioning
confidence: 99%
See 1 more Smart Citation
“…One such material is azurite, Cu 3 (CO 3 ) 2 (OH) 2 , a natural mineral which has been proposed as an experimental realization of the 1D distorted diamond chain model. Interest in the magnetic properties of this material began in the 1950s when an ordered antiferromagnetic (AFM) ground state was observed below 1.9 K. 1,2 From these studies, a detailed description of the magnetic moment structure was never revealed however it has been speculated that the low ordering temperature may result from frustration in the diamond arrangement of spin-1/2 Cu 2+ ions 3 . Early susceptibility measurements indicated that the coupling of spins within the chain could be described with alternating dimers and monomers 4 ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…2, for example, we see a 30% increase in the intensity of the (120) peak on TABLE I: Positional and thermal parameters of Cu3(CO3)2(OH)2 as obtained from the structure refinements of single-crystal (on both D10 and SXD) and powder data in the monoclinic space groups P 21/c. The isotropic thermal parameters Uis are given in units of 100Å 2 . For the refinement several thermal parameters were constrained to be equal.…”
mentioning
confidence: 99%